Mini Review: Quality Control Study of Crude Drug of Justicia gendarussa Burm. f. Leaves as Male Contraceptive - Ummah, Rokhmatul; Wardoyo, Bambang Prajogo Eko; Widyowati, Retno (MPI (Media Pharmaceutica Indonesiana), 2022)
Justicia gendarussa Burm. f. (Gendarussa) leaves contain gendarusin A, which is a potential antifertility agent. Preclinical researches (in vitro, in vivo, and toxicity) and clinical trials have been carried out proving that Gendarussa leaves are safe to be used as a male contraceptive. Quality control of medicine must be carried out from the beginning when selecting crude drugs until the production process. Quality control of the crude drug is needed to maintain the quality, safety, and efficacy of its crude drug. That standardization has been done in Kediri, Mojokerto, and Ponorogo. The research output data used were specific and nonspecific parameters (macroscopic and microscopic assay, determination of ash content, compound levels, etc.). The quality of crude drugs is different in each region. Crude drug from Mojokerto is better than crude drug from Kediri and Ponorogo. This is influenced by environmental difference factors on how plants grow. This review describes the differences in the quality control results of crude drug of Gendarussa from several areas. Hence, in the future, the quality of this plant can be guaranteed to be used as a contraceptive drug.